1993
DOI: 10.1093/jac/32.suppl_b.55
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro antibacterial activity of cefepime: a multicentre study

Abstract: The antimicrobial activity of cefepime, a new broad-spectrum parenteral cephalosporin, was evaluated in vitro against 1757 recent clinical Gram-positive and Gram-negative isolates. Cefepime was active at low concentrations (MIC50 values < or = 0.06 mg/L and MIC90 values < or = 0.12 mg/L) against non-cephalosporinase-producing Enterobacteriaceae (Escherichia coli, Proteus mirabilis, Salmonella spp. and Shigella spp.). For Klebsiella pneumoniae, MICs were between 0.016 and 16 mg/L; the highest MIC values were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 0 publications
2
14
0
1
Order By: Relevance
“…Like Hof [19], Espaze and Reynoud [20], Marklein [21] and Kayser et al [22], we also found some isolates susceptible to cefotaxime [19][20][21][22], We cannot confirm the general efficacy of this antibiotic against L. monocytogenes as described by Ahonkhai et al [23], Larrson et al [24] reported that all of their L. monocyto genes strains were resistant to cefotaxime. All L. monocytogenes strains tested were resistant against ceftriaxone [18,24], The activity of Chemotherapy 1997;43:303-310the fourth generation cephalosporins against L. monocytogenes is also unsatisfactory [25], We found a wide range of MICs of cefpirome; the MIC50 values were in the resistance range. As previously described by others, the cephamycin cefoxitin showed no activity against Listeria in vitro [24], Marklein [21 ] found 1 of 44 L. monocytogenes isolates to be cefoxitin susceptible.…”
Section: In Vitro Susceptibility Of Listeria Monocytogenesmentioning
confidence: 80%
“…Like Hof [19], Espaze and Reynoud [20], Marklein [21] and Kayser et al [22], we also found some isolates susceptible to cefotaxime [19][20][21][22], We cannot confirm the general efficacy of this antibiotic against L. monocytogenes as described by Ahonkhai et al [23], Larrson et al [24] reported that all of their L. monocyto genes strains were resistant to cefotaxime. All L. monocytogenes strains tested were resistant against ceftriaxone [18,24], The activity of Chemotherapy 1997;43:303-310the fourth generation cephalosporins against L. monocytogenes is also unsatisfactory [25], We found a wide range of MICs of cefpirome; the MIC50 values were in the resistance range. As previously described by others, the cephamycin cefoxitin showed no activity against Listeria in vitro [24], Marklein [21 ] found 1 of 44 L. monocytogenes isolates to be cefoxitin susceptible.…”
Section: In Vitro Susceptibility Of Listeria Monocytogenesmentioning
confidence: 80%
“…These dif fer ences en hance the spec trum of bac te ri cidal ac tivity of ce fepime rela tive to all avail able cepha lo sporins (13). Other stud ies have dem on strated that Gram-negative isolates that are re sis tant to one or more third-generation cephalo sporins are sus cep ti ble to ce f epime (14,15). In a re cent Ca na dian sur vey, it was de ter mined that 23% of iso lates of En tero bac ter cloa cae were cef tazidime re sis tant (16).…”
Section: T He Introduction Of Third-generation Cephalo-mentioning
confidence: 99%
“…Therefore, the goal of therapy is to maintain serum drug concentrations above the minimum inhibitory concentration (T > MIC) for the relevant pathogen over most of the dosing interval [1,2]. When aminoglycosides and fluoroquinolones are considered as concentration-dependent antibiotics, b-lactam antibiotics exhibit time-dependent bactericidal activity.…”
Section: N V I T R O a N D E X P E R I M E N T A L R A T I O N A L mentioning
confidence: 99%
“…When aminoglycosides and fluoroquinolones are considered as concentration-dependent antibiotics, b-lactam antibiotics exhibit time-dependent bactericidal activity. Therefore, the goal of therapy is to maintain serum drug concentrations above the minimum inhibitory concentration (T > MIC) for the relevant pathogen over most of the dosing interval [1,2]. Consequently, for therapeutic purposes, it seems justified to update the data in favor of continuous infusion with b-lactam antibiotics, in particular with cefepime, considering its activity mechanism and spectrum.…”
Section: N V I T R O a N D E X P E R I M E N T A L R A T I O N A L mentioning
confidence: 99%